A harlequin ichthyosis pig model with a novel ABCA12 mutation can be rescued by acitretin treatment. (29th March 2019) - Wang, Xiao; Cao, Chunwei; Li, Yongshun; Hai, Tang; Jia, Qitao; Zhang, Ying; Zheng, Qiantao; Yao, Jing; Qin, Guosong; Zhang, Hongyong; Song, Ruigao; Wang, Yanfang; et al.
Abstract: Harlequin ichthyosis (HI) is a severe genetic skin disorder and caused by mutation in the ATP-binding cassette A12 ( ABCA12 ) gene. The retinoid administration has dramatically improved long-term survival of HI, but improvements are still needed. However, the ABCA12 null mice failed to respond to retinoid treatment, which impedes the development of novel cure strategies for HI. Here we generated an ethylnitrosourea mutagenic HI pig model (named Z9 ), which carries a novel deep intronic mutation IVS49-727 A>G in the ABCA12 gene, resulting in abnormal mRNA splicing and truncated protein production. Z9 pigs exhibit significant clinical symptom as human patients with HI. Most importantly, systemic retinoid treatment significantly prolonged the life span of the mutant pigs via improving epidermal maturation, decreasing epidermal apoptosis, and triggering the expression of ABCA6 . Taken together, this pig model perfectly resembles the clinical symptom and molecular pathology of patients with HI and will be useful for understanding mechanistic insight and developing therapeutic strategies.